1983
DOI: 10.1111/j.1365-2125.1983.tb01502.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and liver cirrhosis on the pharmacokinetics of nitrazepam.

Abstract: 1 The effect of age and liver cirrhosis on the pharmacokinetics of i.v. administered nitrazepam was studied in nine healthy relatively young subjects (age 22-49 years), eight healthy elderly (age [67][68][69][70][71][72][73][74][75][76] years) and 12 patients with alcoholic liver cirrhosis (age 39-66 years).2 The elimination half-life of nitrazepam in the elderly subjects was longer than in the young ones but the difference did not reach statistical significance. Mean values (ranges) were 38 (26-64) h and 26 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…However, at least in rats, substantial evidence is presented that in those in vivo situations where extensive biotransformation by aromatic nitroreduction was observed, the intestinal microflora was responsible for it rather than liver systems (Wheeler et al, 1975;Levin & Dent, 1982). An indication that in man the rate of aromatic nitroreduction is small too, may be given by the low clearance of the benzodiazepine derivative nitrazepam, the elimination of which is believed to depend solely on aromatic nitroreduction (Jochemsen et al, 1983). However, also with respect to this drug, the role of the intestinal microflora has been stressed for its clearance (Hewick & Shaw, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…However, at least in rats, substantial evidence is presented that in those in vivo situations where extensive biotransformation by aromatic nitroreduction was observed, the intestinal microflora was responsible for it rather than liver systems (Wheeler et al, 1975;Levin & Dent, 1982). An indication that in man the rate of aromatic nitroreduction is small too, may be given by the low clearance of the benzodiazepine derivative nitrazepam, the elimination of which is believed to depend solely on aromatic nitroreduction (Jochemsen et al, 1983). However, also with respect to this drug, the role of the intestinal microflora has been stressed for its clearance (Hewick & Shaw, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…For nitrazepam, Jochemsen et al (1983b) reported no significant difference between the percentage free in 9 young (13.0% free) and 8 elderly subjects (13.9%). When the study was repeated in another group of 23 subjects aged 30 to 79 years, the average percentage free in subjects over 50 years was higher (14.3%) than in subjects under 50 years (13.1%).…”
Section: I3-blockersmentioning
confidence: 86%
“…Impairment of the rate of drug elimination in the elderly has been demonstrated for those benzodiazepines which are primarily oxidized (e.g. diazepam, chlordiazepoxide, desalkylflurazepam and desmethyldiazepam) (Divoll Allen et al, 1980;Greenblatt et al, 1980aKlotz et al, 1975;Klotz & Muller-Seydlitz, 1979;Roberts et al, 1978) and for nitrazepam (Jochemsen et al, 1983b;Kangas et al, 1979). Age, on the other hand, has little, if any, effect on the disposition of benzodiazepines, for which drug conjugation is the primary metabolic step Greenblatt et al, 1979Greenblatt et al, , 1980bKrauss et al, 1978;Shull et al, 1976) Benzodiazepines are frequently prescribed for elderly patients and age related changes in clinical effects may be due to alterations in protein binding, distribution or clearance.…”
Section: Results)mentioning
confidence: 99%